ENSURING INTERETHNIC HARMONY AND SOLIDARITY IN UZBEKISTAN EFFECTIVE WORK ON THE ROAD - Soliyev Umidjon (Galaxy International Interdisciplinary Research Journal, 2021)
This article discusses interethnic harmony and its effective functioning in Uzbekistan, human life, values, interreligious harmony.